Edukasi pentingnya pola asuh demokratis bagi perkembangan anak usia dini - Putri Zalika Laila Mardiah Kesuma; Ratika Febriani; Rafa Desinta (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Education on the importance of democratic parenting for early childhood development. Parenting styles play a very important role in the growth and development of children, not only in physical, cognitive, and socio-emotional aspects but also in spiritual aspects. The parenting styles experienced by children in early childhood serve as the foundation for the development of behaviors and values they will choose later in adolescence and adulthood. This community service activity is located in Pipa Reja Village, Kemuning District, Palembang. Through this activity, it is hoped that mothers will gain knowledge about the role of democratic parenting in their children's development. The activity consisted of direct counseling about the types of parenting and the importance of democratic parenting for children's development. The participants' knowledge level was measured through pre-tests and post-tests using questionnaires related to the counseling material for 25 participants. The results showed an increase in participants' knowledge from 32% to 84%. The participants were enthusiastic about the activity and actively engaged in the discussion session. All participants followed the counseling process until the community service activity was completed. This educational community service activity was able to enhance the knowledge and awareness of the community about the importance of democratic parenting for early childhood development.